Histopathological Evaluation of Colorectal Carcinomas Status in Manipur, India - Laishram, Rajesh Singh; Kaiho, Nisa; Shimray, Rachel; Devi, Sorokhaibam Babina; Punyabati, Pukhrambam (International Journal of Pathology, 2018)
Objective: To study the distribution of colorectal carcinomas (CRC) with special emphasis on age, sex, site andhistological grading.Study Design: Retrospective study.Place & Duration: Department of Pathology, Regional Institute of Medical Sciences (RIMS), Imphal, Manipur,India, from January 2004 to December 2009.Materials & Methods: Materials were collected from subjects first diagnosed as colorectal carcinomas inhistopathology section and then the medical files were reviewed. Variables like age, sex, religion, relevant past /family history, tumor location, disease stage (Dukes’ staging) were assessed. The findings were then analysed.Results: There were 54 patients with colorectal carcinomas during this 6 year period. 29 cases (53.71%) weremales while 25 cases (46.29%) were females with a male to female ratio of 1.16:1. The disease was mostcommonly seen between 60-69 years age group. The rectum was the most common affected site contributing to53.71% (29 cases) followed by ascending colon with 12 cases (22.22%). 38.88% of lesions (21 cases) were stageC and above i.e. involvement of local lymph nodes and distant metastasis. When we compared patients above 50years of age to those under 50 years of age, we found that the disease usually presented with poorer grades ofdifferentiation and more advanced stage in those below 50 years compared to those above 50 years.Conclusions: This study showed that bowel cancers are not rare as previously believed. Routine screening forbowel cancer in all risk patients should be carried out regularly so as to detect cancer early.